Freedom of expression vs right to reputation, when the affected party is a member of the Judiciary (analysis to the ECHR judgment in the case of Benítez Moriana and Íñigo Fernández v. Spain (March 9, 2021)) (Revista de Estudios Europeos, 2022)
.
Keywords: Freedom of expression; right to reputation; European Court of Human Rights